Impact of different levels of caries experience on the quality of life of preschool children and their families in Pimpri, Pune: A cross-sectional study - Shruti Nair; Pradnya Kakodkar; Sahana Hegde Shetiya; Ladusingh Rajpurohit; Sonal Kale (Wolters Kluwer Medknow Publications, 2018)
Background: As per WHO, it is important to measure quality of life indictors along with the clinical disease measurement. Objective: The objective of this study is to evaluate the impact of different levels of caries experience on the quality of life of preschool children and their families assessed using the Marathi Early Childhood Oral Health Impact Scale (ECOHIS). Materials and Methods: The Marathi version of ECOHIS was developed through a standard translation and back translation procedure. A total of 145 preschool children underwent an oral examination, and their caries experience was recorded (decayed, missing, and filled teeth [dmft]) and their parents filled the Marathi ECOHIS questionnaire. The overall ECOHIS score was calculated for each child. Based on the dmft scores, three groups were made (0, 1-3, >3). Impact was assessed by comparing the mean Marathi ECOHIS scores of the three dmft groups using Kruskal-Wallis test with post hoc analysis at 5% level of significance. Results: The overall prevalence of dental caries in the present study was 73.10%. Mean dmft was 3.16 ± 3.61. The overall child impact ECOHIS score was 7.54 ± 8.40, and family impact score was 2.50 ± 3.33. The child impact and family impact ECOHIS score significantly differed in the three dmft groups (P < 0.001). Children with dmft >0, significantly had higher child impact and family impact score as compared to those with dmft = 0. However, there was no difference in the scores between dmft 1 and 3 and dmft >3. Conclusion: This study showed that the Marathi ECOHIS significantly discriminates amongst children with and without caries but does not differentiate between children with lower dmft (1-3) and higher dmft (>3) levels.